Resolving the conflict in the reasons for gaining consideration for the united ownership (A comparative study) - Abdul- Khader Abbas, Researcher. Ali; Raisan Jader, Prof. Dr. Ghani (Basra studies journal, 2024)
Talking about the reason of acquiring ownership in this research is related to its comprehensive nature, or what is called dependency. Competition may only arise between a contract and another contract, or a code and another code, or between possession and another possession, or between a will and a commandment...etc. This shared self-existence between them. The contract and the contract share independence together, or the contract and the will as being non-legal. However, a dispute may arise between a contract and an inheritance, or between pre-emption and a contract, or between a judiciary and a contract, or between pre-emption and an inheritance, or between a pledge and a contract...etc., and this dispute arises from the combination of this specific knowledge and this quantitative consideration, Many technical texts that rely on these entities - such as seizure, possession, contract... and other causal entities - are the method that seeks to obtain the ownership that the legislator defends. This crowding may be a theoretical rivalry that is rooted in the mind of the legislator or jurist, or it may be an actual crowding that is clear from the law and reality, and each of the crowding has a solution that suits it.